Sighting of the Rare Brilliant Silverspot, Issoria mackinnoni (de Niceville, 1891), (Lepidoptera : Nymphalidae : Heliconiinae) in Arunachal Pradesh, India - Sharma, Narender; Haniya, Tage (Indian Forester, 2023)
No Abstract.